2005
DOI: 10.4049/jimmunol.175.4.2534
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous Arg753Gln Polymorphism of Human TLR-2 Impairs Immune Activation by Borrelia burgdorferi and Protects from Late Stage Lyme Disease

Abstract: Lyme disease (LD) is caused by Borrelia burgdorferi and displays different stages, including localized, early disseminated, and persistent infection, all of which are associated with profound inflammatory reactions in the host. Induction of proinflammatory cytokines by B. burgdorferi is mainly mediated by outer surface proteins interacting with TLR-2/TLR-1 heterodimers. In this study, we show that TNF-α induction by Borrelia lysate was impaired in heterozygous TLR-2 knockout mice, while reactivity to lipoteich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(93 citation statements)
references
References 49 publications
3
87
0
Order By: Relevance
“…Notably, polymorphism of residue Arg-753 (R753Q) has been linked with the susceptibility to Staphylococcal, Borellia sp., and Mycobacterium sp. and has also been associated with acute rheumatoid fever in children (23)(24)(25)(26)(27). Thus our modeling studies also suggest a potential explanation for the observed decreased activity of the R753Q polymorphism.…”
Section: Resultssupporting
confidence: 63%
“…Notably, polymorphism of residue Arg-753 (R753Q) has been linked with the susceptibility to Staphylococcal, Borellia sp., and Mycobacterium sp. and has also been associated with acute rheumatoid fever in children (23)(24)(25)(26)(27). Thus our modeling studies also suggest a potential explanation for the observed decreased activity of the R753Q polymorphism.…”
Section: Resultssupporting
confidence: 63%
“…The TLR2 polymorphism R753Q may predispose to infection with S. aureus [102] or M. tuberculosis [103]. Finally in a very recent publication, it was demonstrated that the same R753Q polymorphism in TLR2 protects from late-stage Lyme disease [104]. Collectively, these human studies have confirmed the important role that TLRs play in a protective immune response and are generally consistent with the information obtained from gene-deficient mice.…”
Section: The Functions Of Tlrs In the Pathogenesis Of Bacterial Infecsupporting
confidence: 75%
“…Several SNPs have been associated not only with cancer risk [17] but also a susceptibility to several diseases, such as HIV infection [18,19], urinary tract infections (cystitis and pyelonephritis) [20], Hansen's disease [21,22], Lyme disease [23], Legionnaires' disease [24,25], asthma [26,27], atopic syndrome [27], sepsis [28] and tuberculosis [29]. In addition, cellular studies have revealed the effect of TLR polymorphisms on TLR ligand-induced innate immune responses.…”
Section: Tlr Family and Its Biological Functionsmentioning
confidence: 99%